2017
DOI: 10.2903/j.efsa.2017.4972
|View full text |Cite
|
Sign up to set email alerts
|

Human and animal dietary exposure to T‐2 and HT‐2 toxin

Abstract: T-2 toxin (T2) and HT-2 (HT2) toxin are trichothecenes, which form part of the group of Fusarium mycotoxins. Food and feed samples used to estimate human dietary and animal exposure were reported either as the individual results for T2 and/or, HT2, and/or as the sum of the two. The highest concentrations were reported in oats and oat-containing commodities. Very high levels were reported in a small number of data on specific plant-and herb-based dietary supplements. In humans, the mean chronic dietary exposure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
35
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(36 citation statements)
references
References 17 publications
1
35
0
Order By: Relevance
“…Given the rapid in vivo conversion of T-2 to HT-2, in vivo toxicity of T-2 is recognized to include that of HT-2. 31 According to a recent EFSA opinion, cats are extremely sensitive to this mycotoxin category, 40 and probably for this reason, some years ago, the European legislation was implemented with a guidance value for T-2 + HT-2 only referred to this last species. 25 Recently, some studies have reported a wide occurrence of T-2 and HT-2 in cereals and animal feed.…”
Section: Discussionmentioning
confidence: 99%
“…Given the rapid in vivo conversion of T-2 to HT-2, in vivo toxicity of T-2 is recognized to include that of HT-2. 31 According to a recent EFSA opinion, cats are extremely sensitive to this mycotoxin category, 40 and probably for this reason, some years ago, the European legislation was implemented with a guidance value for T-2 + HT-2 only referred to this last species. 25 Recently, some studies have reported a wide occurrence of T-2 and HT-2 in cereals and animal feed.…”
Section: Discussionmentioning
confidence: 99%
“…PMTDI was established for T-2 and HT-2 alone or in combination of 0.06 µg/kg bw per day obtained in a 3-week dietary study in pigs [ 128 ]. A new group TDI of 0.02 µg/kg bw was established by EFSA for the sum of T-2 and HT-2 based on an in vivo sub-chronic toxicity study with rats [ 129 ].…”
Section: Mycotoxin Exposure Assessment and Risk Characterizationmentioning
confidence: 99%
“…For the sum of T-2 and HT-2, the TDI has been set at 0.02 μg/kg bw per day [ 129 ], which means 1.4 μg for a 70 kg human. In the worst-case scenario, for a human of this weight, a single RDD of 3 capsules of MT-based supplement has accounted for 1590% of TDI [ 3 ].…”
Section: Mycotoxin Exposure Assessment and Risk Characterizationmentioning
confidence: 99%
“…Hence, legal maximum limits for the presence of mycotoxins in feed and food have been set in Europe and other parts of the world to protect animal and human health [8]. In spite of these limits, human exposure assessments in Europe have shown that the intake of some mycotoxins is currently above the tolerable daily intake for certain vulnerable groups [7,9]. The past four years, two large European Union's Horizon 2020 funded research and innovation projects focussed on further reducing mycotoxin contamination in feed and food commodities like wheat (www.mycokey.…”
Section: Introductionmentioning
confidence: 99%